THE INFLUENCE OF BINAHONG LEAVES (ANREDERA CORDIFOLIA) ON HEALING OF FLOUR ALBUSON FEMALE STUDENTSOF CLASS XI SMAN 1 PACIRAN LAMONGAN DISTRICT - Iswatun, Iswatun; Pangestu, Anestasia; Nasir, Abdul; Lailiyah, Nazilatul; Aris, Arifal (Universitas Airlangga, 2020)
Introduction: One problem of adolescents at the age of 11-20 years who have not entered adulthood is fluor albus. In the initial survey, more than half of the students (70%) had vaginal discharge problems. This study aimed to determine the effect of binahong leaves decoction (AnrederaCordifolia) on healing Flour Albuson female Student of class XI SMAN 1 Paciran, Lamongan District. Methods: The design used pre-experimental method with one grouppre test and post test. The population was all female students who had fluor albus of 34 children and sample of 25 children with consecutive sampling techniques that the inclusion creteria. The data were analyzedusing Wilcoxon Sign Rank Test, with significance level of p <0.05 using SPSS V program 22.0. Results: The results of statistical tests showed that the values of Z: -4.613b and p = 0.000 where p <0.05, H1 was accepted, meaning that there was an effect of binahong leaves decoction (AnrederaCordifolia) on healing Flour Albus. This study indicated that binahong leaf decoction herbs can reduce and even healing fluor albus with good personal hygiene behavior.